Contemporary Latina/o theater : wrighting ethnicity - Rossini, Jon D., 1971- (Theater in the Americas., 2008)
In Contemporary Latina/o Theater, Jon D. Rossini explores the complex relationship between theater and the creation of ethnicity in an unprecedented examination of six Latina/o playwrights and their works: Miguel Piñ ero, Luis Valdez, Guillermo Reyes, Octavio Solis, José Rivera, and Cherrí e Moraga. Rossini exposes how these writers use the genre as a tool to reveal and transform existing preconceptions about their culture. Through " wrighting"--The triplicate process of writing plays, righting misco.